The foundations of Islamic banking : theory, practice and education - Mohamed Ariff, 1942-; Iqbal, Munawar (Cheltenham, UK ; Northampton, MA ; Edward Elgar, 2011)
Examines the roots of the principles of ethical Islamic financial transactions, which have evolved over several millennia, on issues including usury, interest rates, and financial contracting for funding enterprises, mortgages, leasing and other transactions. Regulatory and governance issues are discussed, and the practice and operation of Islamic financial institutions are explained via three distinct case studies. The final chapter looks at what steps are being taken to provide professional accreditation to Islamic banking professional personnel and prescribes requirements for training in this growing industry. From publisher description.
Introduction to Islamic financial institutions / Mohamed Ariff, Munawar Iqbal -- Ethics-based financial transactions : an assessment of Islamic banking / Mohamed Ariff -- Ethical principles in Islamic business and banking transactions / Mervyn K. Lewis -- Adapting understanding of riba to Islamic banking : some developments / Abdullah Saeed -- Development, history and prospects of Islamic banking / Ishaq Bhatti, Maria Bhatti -- Corporate governance and Islamic banks / Michael T. Skully -- Performance of Islamic banks and conventional banks / Mohamed Ariff, Mohammad K. Badar, Shamsher M., Taufiq Hassan -- Shariʼaah-consistent investment vehicles in Malaysia / Kabir Hassan, Eric Girard -- Takaful insurance : concept, history, and development challenges / Syed Othman Alhabshi, Shaikh Hamzah Razak -- Usury and its critics : from the Middle Ages to modernity / Constant Mews, Adrian Walsh -- Riba and interest in Islamic banking : an historical review / Raquib Zaman --Tensions in Christian financial ethics : an historical overview / Ibrahim Abraham -- Human capital development in Islamic finance : initiatives and challenges / Syed Hamid Aljunid.
Includes bibliographical references and index.
Keywords: Banks and banking -- Islamic countries; Finance -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Banking law (Islamic law); Finance -- Religious aspects -- Islam